Analisis HPP dan Penetapan Harga Jual Sepeda Gunung ABC Pada PT XYZ - Prasetyo, Hendra Dwi; Sekaryanti, Dewi Ayu (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
A bicycle is one of the best of transportation that never make it in the time for it .In line with the modern era, cycling is now a new hobby of the urban population especially in kota sidoarjo and surabaya .Moreover in the pandemic as the last two years the bicycle take their time again because of cycling believed to to make body to be to be healthier. Research on Cost of Goods Sold (COGS) this abc aims to understand the determination of the cost of goods sold and determination of selling prices he would do to pt xyz .The research was conducted in pt object xyz mountain bike products as a seller of abc .Data analysis was conducted using a method of descriptive quantitative namely the data obtained by next analyzed and accounted for , so that it result can respond to the formulation of the issues to be examined , so that we can take the conclusions from the data processing. The research results show that the determination of the cost of the production of have done well and precisely so able to select the selling price of any products correctly .The experimental show that it get had good profit according to the company need, but it will be more optimal if the percentage of profit can be increased so the company can be developed any further